Konsep Qathiy dan Zhanniy Serta Implikasinya dalam Memahami Al-Quran - Rosyanti, N. Imas (UIN Sunan Gunung Djati Bandung, 2009)
Difference of opinion is not all along can evoke blessing, in many narrow grasp case to therewith source islam its teaching can create Islamic people conflicts that dont be expected. Therefore to settle pretty much appearance it that problem in the future agents dawah ought to membekali self exhaustively methodologicaling ability to understand Islamic teaching source comprises in it concern qoth iy and dhonniy of Al Qur an text.Keywords:Qathiy, Zhanniy, Metode Tafsir Al-Quran